A Spatial Mapping for Profitability Consideration of Rental Houses in South Jakarta - Salma, Yuriduna; Sakti, Trie (BHUMI: Jurnal Agraria dan Pertanahan, 2024)
The study aims to investigate the relationship between these spatial factors and the profitability of rent houses in the South Jakarta region. The population of South Jakarta reached 2.235.606 people as of 2023, with a percentage of occupying owned residential buildings of 51,36%. Estimates indicate that only approximately 1,148,207 people currently reside in private assets. Rental prices need to be considered based on the strategic location to minimize the risk of rental house business owners suffering losses. The imbalance in the supply and demand of the residential market will cause the availability of land in productive areas to be increasingly limited. The existence of an imbalance in market supply and demand can be an opportunity for prospective property entrepreneurs in the field of rental houses. This study is based on the rise in the price of houses, which leads to a lower level of community ownership of the houses. The analysis was carried out by calculating income predictions using multiple linear regression methods and spatial analysis between rental houses and the accessibility of public facilities in South Jakarta City. The results obtained indicate that the accessibility of public facilities in Setia Budi Sub-district provides an opportunity for high income. Keywords: Boarding House, Income Rediction, Multiple Linear Regression, Spatial Analysis